Anisotropic flow of charged hadrons, pions and (anti-)protons measured at high transverse momentum in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Constantin, Paul; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; et al. (Physics letters, 2013)
The elliptic, v2, triangular, v3, and quadrangular, v4, azimuthal anisotropic flow coefficients are measured for unidentified charged particles, pions, and (anti-)protons in Pb-Pb collisions at sNN=2.76 TeV with the ALICE detector at the Large Hadron Collider. Results obtained with the event plane and four-particle cumulant methods are reported for the pseudo-rapidity range |η|<0.8 at different collision centralities and as a function of transverse momentum, pT, out to pT=20 GeV/c. The observed non-zero elliptic and triangular flow depends only weakly on transverse momentum for pT>8 GeV/c. The small pT dependence of the difference between elliptic flow results obtained from the event plane and four-particle cumulant methods suggests a common origin of flow fluctuations up to pT=8 GeV/c. The magnitude of the (anti-)proton elliptic and triangular flow is larger than that of pions out to at least pT=8 GeV/c indicating that the particle type dependence persists out to high pT.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Constantin, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, K. Koch, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, S. Radomski, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, S. Vallero, Y. Wang, B. Windelband, A. Zimmermann und weitere 937
Gesehen am 30.04.2021